Insect pests in tropical forestry - Wylie, F. R.; Speight, Martin R. (Cambridge, MA : CABI, 2012)
'The management of tropical forest ecosystems is essential to the health of the planet. This book addresses forest insect pest problems across the world's tropics, addressing the pests' ecology, impact and possible approaches for their control. Fully updated, this second edition also includes discussions of new areas of interest including climate change, invasive species, forest health and plant clinics. This work is an indispensible resource for students, researchers and practitioners of forestry, ecology, pest management and entomology in tropical and subtropical countries.'--pub. desc.
Speight's name appear first on the earlier edition.
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Forest insects -- Tropics; Forest insects -- Control -- Tropics